2004
DOI: 10.5688/aj680493
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of PharmD Students Towards a Cumulative Examination: The Milemarker Process

Abstract: Cumulative ExaminationsProfessional organizations in various fields currently make use of annual cumulative and comprehensive examinations to assess the quality and level of education imparted to students. A few pharmacy schools have also established their own annual cumulative examinations that cater to programmatic goals in order to gauge student learning, student knowledge, and student preparedness for progressing into different stages of the academic curricula. 3 In a study conducted in 1998, 9 out of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 7 publications
(9 reference statements)
1
21
0
Order By: Relevance
“…The authors also emphasized the need for intervention strategies to create a positive feeling for students towards these assessments. 20 Our study provides evidence of a successful intervention to enhance student performance on cumulative examinations.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The authors also emphasized the need for intervention strategies to create a positive feeling for students towards these assessments. 20 Our study provides evidence of a successful intervention to enhance student performance on cumulative examinations.…”
Section: Discussionmentioning
confidence: 71%
“…In a study conducted by Sansgiry et al 20 to determine the perceptions of PharmD students, the authors concluded that in spite of the increasing importance of cumulative examinations, students had a negative attitude about these assessments. The authors also emphasized the need for intervention strategies to create a positive feeling for students towards these assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples are: benchmarking results of year-end examinations in comparison to other schools in the nation, determining progress, and (most relevant to the present manuscript) identifying students who would benefit from remediation. 36,37 In a year-end assessment examination, the questions are either tied to a school's outcomes or directly to a course. This can help identify weaknesses or a loss of knowledge over time by students.…”
Section: American Journal Of Pharmaceuticalmentioning
confidence: 99%
“…(For more information on year-end examinations, consult one of the articles written by faculties from the Texas Tech University or University of Houston. 36,39 )…”
Section: American Journal Of Pharmaceuticalmentioning
confidence: 99%